(untitled) (Kairaranga, 2008)
The Incredible Years parent training programme is a research-based therapy which aims to help families improve the behavior of children with conduct difficulties in the early years, while the behaviour is malleable (Webster-Stratton & Reid, 2003). The short-term goals of the programme are to reduce conduct problems in children by increasing parental competence and strengthening families (Webster-Stratton, 2000). The programme was developed by the University of Washington’s Parenting Clinic, USA and was introduced to the Tauranga community in 2002, via the research of Lees (2003). Due to the success of the programme trialled in Lees’ research, it was rapidly embraced by agencies and community organisations. Hamilton’s (2005) research is summarised if this article and was inspired by the rapid expansion of, and enthusiasm for, the Incredible Years parent training programme in Tauranga. Rather than following participants experiences within the programme, the researcher interviewed the facilitators. The perspective taken was that most of the programme facilitators are highly qualified psychologists and social workers who collectively have an enormous amount of knowledge, experience and insight. The researcher captured the observations and insights of the facilitators who, from their experience working with the programme, made valuable contributions to the identification of the barriers to the programme’s success in Tauranga, the appropriateness of this empirically supported manual-based therapy in New Zealand’s bicultural environment, and the value of the programme itself. The Incredible Years parent training programme was found to be highly successful in Tauranga as it provided a supportive group environment in which parents could share concerns and ideas, and it was adaptable to different cultural and individual needs